Business dynamics of a business group in Peru: The Romero case (1890-1985) - Reaño A., Germán; Vásquez H., Enrique (Universidad del Pacífico, 1986)
The article presents a discussion of the different variables of analysis of an economic group: the strategies of growth (integration, diversification, and relation with the financial system) as well as the levels of relation with the State, foreign capital and other economic national groups. The outline of the analysis proposed is applied studying the historical development of the Romero group since its establishment in Catacaos (Piura) until the organizational structure obtained in 1985. The authors finish with a global interpretation of the growth dynamic of the Romero group, establishing, tentatively, causality relations from the variables presented in the outline of analysis.